Takotsubo syndrome: How the broken heart deals with negative emotions - Carina Klein; Simon Leipold; Jelena-Rima Ghadri; Stjepan Jurisic; Thierry Hiestand; Jürgen Hänggi; Thomas F. Lüscher; Lutz Jäncke; Christian Templin (NeuroImage: Clinical, 2020)
Objectives: Patients suffering from Takotsubo syndrome have a higher prevalence of anxiety and depressive disorders compared to those with acute myocardial infarction and might thus show impaired regulation and processing of emotions. Methods: In this cross-sectional study, neural activity during an emotional picture processing task was examined in 26 Takotsubo patients (on average 27 months after the Takotsubo event) and 22 healthy age- and gender-matched control subjects undergoing functional magnetic resonance imaging. Imaging data were analyzed with two complementary approaches: First, univariate analysis was used to detect brain regions showing condition-specific differences in mean neural activity between groups. Second, multivariate pattern analysis was applied to decode the experimental conditions from individual activity patterns. Results: In the univariate analysis approach, patients showed lower bilateral superior parietal activity during the processing of negative expected pictures compared to the control subjects. The multivariate pattern analysis revealed group differences in decoding negative versus neutral pictures from a widespread network consisting of frontal, parietal, occipital, and cerebellar brain regions. Additionally, differences in decoding the expectation of a negative versus positive upcoming picture were observed in the visual cortex. Conclusion: The lower involvement of brain regions observed in Takotsubo patients suggests an impairment in emotion regulation, which might be of etiological importance in this brain-heart disease. Keywords: Broken heart syndrome, Emotion regulation, Picture processing, Brain-heart connection